Перспективи використання німецького досвіду в організації бакалаврської підготовки за спеціальністю «Економічна педагогіка» - Melnyk, Oksana (Professional Pedagogics, 2017)
At times when Ukraine strives to integrate into the European Union, the relevance of research and implementation of the best European practices is especially high, therefore the given article suggests the comparative overview of study programs in Economics and Business Education from the German universities with the intention of using the best practices in the transformation of study programs in Vocational Education and Economics at Ukrainian universities. The research has been conducted on the basis of the study programs of two German and two Ukrainian universities. After the analysis the recommendations of the usage of the German experience in organizing the Bachelor programs in Economics and Business Education have been outlined. They foremost concern such areas of study as Economics and Humanitarian Sciences. Regarding perspectives of the employment of bachelor graduates in Ukraine, it is recommended to strengthen the fundamental knowledge in economics by means of the increase of ECTS points in economics courses. The comparative analysis has showed that German universities pay considerable attention to fundamentalization of economic knowledge. Such an approach is consistent with the principle of polyvalence of the study on Economics and Business Education. It has been possible to implement because the humanitarian courses are included into the elective block, i.e. for student’s choice. Finally, taking into account the importance of research work during the study it is highly recommended to increase research and scientific work in the study plans of Ukrainian universities.